Measuring the impact of online reviews on consumer purchase decisions – A scale development study. (September 2022) - Fernandes, Semila; Panda, Rajesh; Venkatesh, V.G.; Swar, Biranchi Narayan; Shi, Yangyan
Abstract: Consumers' exposure to online reviews influences their online retail shopping behavior. They search for reviews while evaluating products for purchase decisions. Past studies have indicated that online reviews affect the credibility and trust of the sellers and the products they sell on online platforms. Keeping this in view, the current paper aims to develop and validate a scale to understand the impact of online reviews on consumer purchase decisions. Data were collected from 431 young online shoppers for this research. The initial exploratory factor analysis (EFA) results helped identify four factors, viz. source credibility, volume, language and comprehension, and relevance which constitute the scale. The scale was validated by confirmatory factor analysis (CFA). The study's findings fill the gap of having a standardized scale that online retailers can use as indicators to assist consumers in their online decision-making. The discussions and implications support consumers' susceptibility to online reviews, an essential source for product and brand information in facilitating online consumers' purchase decisions.